Participatory research and action: a methodological tool for the understanding and transformation of university practice - Revelo-Rosero, Jorge (2021)
This research focuses on the study of the Participatory Action Research (PAR) methodology as part of the academic training of students in the Early Education Career. There is no evidence of studies that support the application of the I-AP at a higher level, therefore, it is an objective of this research to determine whether the I-AP is a methodology that improves the educational practice of students in the Early Childhood Education Career at the Technical University of Machala (UTMCH), given that this methodology today is giving the educational community answers that are aimed at solving the problems that arise in the research. Within its application, two important processes are combined in the classroom, that of knowing and that of acting, involving students in both. Like other participatory approaches, this one provides communities with a method to analyze and better understand the reality of the population, its problems, needs, capacities and resources; and, it allows them to plan actions and measures to transform and improve it. A descriptive, non-experimental research design with a qualitative approach was applied. Subsequently, a descriptive analysis was made of the information collected through a semi-structured interview of seven open questions. The results obtained showed a greater interest and expectation of what will be taught in the subject of Participatory Research and Action: Lesson Study within the Career as part of their academic training.